Sediment Dynamics and Bed Stability in Step‐Pool Streams: Insights From 18 Years of Field Observations - Marwan A. Hassan; Matteo Saletti; Conor McDowell; Wenqi Li (Water Resources Research, 2023)
Abstract Step‐pools are a common morphology in gravel‐bed streams with gradients between 3% and 30%, where coarse sediment and wood are present. Recent experimental work has offered insight on the formation of step‐pools, flow resistance, and interactions between sediment transport and channel morphology. However, field observations are sparse and often limited by short observation periods. Using an extensive 18‐year data set, we examine controls on sediment mobility, step stability, and sediment storage in East Creek, a step‐pool reach in British Columbia. Event bedload yield correlated with peak flow and ranged over two orders of magnitude. For most events, bedload grain‐size was finer than the grain size distribution of the sediment found in pools. Fractional sediment mobility was independent of the flow magnitude and controlled by sediment supply. The large stones that comprise the steps were generally mobile during large events (>10‐year recurrence interval), although the largest ones were not. Despite the movement of large stones, the skeleton of the steps remained in place even during an event with a near 125‐year recurrence interval. Temporal trends in sediment storage in pools show that most events cause negligible changes in sediment storage. Our field observations indicate that the step‐pool morphology of East Creek is stable, as the morphology and shape of the steps persisted under a wide range of flows. The overall stability of the reach is confirmed by observed trends in bedload yield and particle mobility.